2020
DOI: 10.1186/s13033-020-00401-7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a mental health literacy course for Arabic speaking religious and community leaders in Australia: effects on posttraumatic stress disorder related knowledge, attitudes and help-seeking

Abstract: Background: Australia is an ethnically diverse nation with one of the largest refugee resettlement programs worldwide, including high numbers of refugees with an Arabic speaking background. Evidence suggests that refugees can demonstrate high levels of psychological distress and are at a higher risk of developing mental illness such as posttraumatic stress disorder (PTSD) and major depressive disorder (MDD). Notwithstanding, research has also shown Arabic speaking refugees have lower levels of professional hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Instead, lower use may be driven by stigma, ignorance, misidentification or somatization of psychiatric symptoms, ignorance of existing support services and referral chains, use of religious sources of mental health support (including holy books and religious leaders), unwillingness to revisit traumatic memories, and avoidance of emotional discomfort. 19 , 20 Other reasons could be a lack of time and/or financial resources, language and/or cultural barriers, unstable housing, or a lack of trust. 21 A study in Australia 22 reported that two-thirds to one-half of all refugees do not seek help for emotional problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, lower use may be driven by stigma, ignorance, misidentification or somatization of psychiatric symptoms, ignorance of existing support services and referral chains, use of religious sources of mental health support (including holy books and religious leaders), unwillingness to revisit traumatic memories, and avoidance of emotional discomfort. 19 , 20 Other reasons could be a lack of time and/or financial resources, language and/or cultural barriers, unstable housing, or a lack of trust. 21 A study in Australia 22 reported that two-thirds to one-half of all refugees do not seek help for emotional problems.…”
Section: Discussionmentioning
confidence: 99%
“…More funding should be directed toward programs to raise levels of mental health literacy among refugees and among religious leaders and priests from whom refugees seek mental health advice. 20 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…The present study is a subset of a dataset evaluating an MHL training course for Arabic-speaking religious and community leaders in South Western Sydney, Australia [42]. A total of 54 participants undertook a 6 h MHL training workshop (see Slewa-Younan and colleagues [42] for an overview of the intervention and power analysis).…”
Section: Participants Procedure and Study Designmentioning
confidence: 99%
“…The present study is a subset of a dataset evaluating an MHL training course for Arabic-speaking religious and community leaders in South Western Sydney, Australia [42]. A total of 54 participants undertook a 6 h MHL training workshop (see Slewa-Younan and colleagues [42] for an overview of the intervention and power analysis). Of these individuals, 52 participants completed a self-report survey prior to and immediately following training but this study only utilised the pre-intervention survey responses.…”
Section: Participants Procedure and Study Designmentioning
confidence: 99%
“…Taking causal beliefs into consideration in mental health care has proven useful at several stages of counselling and treatment (Dinos et al, 2017 ; Petrie & Weinman, 2006 ). Causal beliefs can influence symptom severity (Massad & Hulsey, 2006 ), whether a person seeks treatment (Sheikh & Furnham, 2000 ; Spoont, Sayer, & Nelson, 2005 ), and what kind of treatment is sought (Hinton & Kirmayer, 2013 ; Slewa-Younan et al, 2020 ). Particularly in transcultural settings, but also in general, a sensitive approach to causal beliefs is the basis for effective interventions, as patient satisfaction and treatment effectiveness increase when patient and practitioner concur about a model (Benish, Quintana, & Wampold, 2011 ; Callan & Littlewood, 1998 ).…”
Section: Introductionmentioning
confidence: 99%